Resenha: ANTUNES, António Lobo. O meu nome é Legião. Lisboa: Dom Quixote, 2007. (Revista do Centro de Estudos Portugueses, 2007)
Resenha: ANTUNES, António Lobo. O meu nome é Legião. Lisboa: Dom Quixote, 2007.